Assessment of the Awareness of COVID-19 among the Students Enrolled in Different Medical Universities of Pakistan: A Cross Sectional Survey - Ali, Aadil Ameer; Haq, Noman; Naqi, Sana; Hussain, Amjad; Rafique, Muhammad; Ismail, Muhammad; Ahmad, Taufiq; Ishaque M.R, Muhammad; Yasmeen, Shabana (AL-Kindy College Medical Journal, 2021)
Background: The study was designed for the assessment of the knowledge of medical students regarding pandemics. In the current designed study, the level of awareness was checked and the majority of students were found aware of SARS-CoV and SARS-Cov2 (Covid-19).Objective: To assess the awareness of SARS-CoV and SARS-Cov2 (Covid-19) among medical students of Pakistan.Subjects and Methods: A cross-sectional survey was carried out in different universities of Pakistan from May to August 2020. A self-constructed questionnaire by Pursuing the clinical and community administration of COVID-19 given by the National Health Commission of the People's Republic of China was used among the 831 students who are enrolled in different medical universities of Pakistan and SPSS version 23 was used to analyze the data.Results: The majority (n=440, 52.9%) were male, (n=525, 63.2%) having age between 18 to 23years and (n=682, 82.1%) were unmarried. In educational status (n=501, 60.3%) were undergraduate and (n=214, 25.8%) were students of MBBS. After checking the residential status (n=343, 41.3%) were the permanent residents of Balochistan province. During the assessment of awareness towards Covid-19 results showed that (n=801, 96.4%) were aware regarding Covid-19.Conclusion: This study finalized that the students enrolled in different medical universities of Pakistan were aware of the Covid-19. The observed awareness can be due to qualitative education especially in the domain of disease prevention, which has been provided by the educational institutions of Pakistan in collaboration with the Ministry of Health. Keywords: Awareness, Covid-19, Medical students, Pakistan.